The effect of Malaysia General Election toward stock market: Malaysian cases / Melvin Hans Mikol - Mikol, Melvin Hans (2017)
The 2013 general election in Malaysia has caused changes in the political structure of Malaysia. The incumbent government, Barisan National, failed to acquire two-thirds majority in the parliament, thus losing their once-absolute control over legislative power. Amidst the political uncertainty, it is the aim of this research paper to investigate if there is an impact of 13th Malaysian General Election on the stock market of Malaysia upon the arrival of 13th Malaysian General Election. Event study methodology, along with an event study is used to capture the impact of 13th Malaysian General Election on its stock market. As the result before and after the General Election shows that there is significant effect on the stock market. Meanwhile during the general election shows that insignificant effect on stock market return.